Evaluation Method of Ecological Tourism Carrying Capacity of Popular Scenic Spots Based on Set Pair Analysis Method - Xiangrong Yan (Journal of Advanced Transportation)
By making adaptive adjustments to the tourism activities and tourism structure carried out in the tourist area, the natural resources of the scenic area can be protected while pursuing economies of scale. Moreover, it achieves a benign interaction between scenic spot development, planning, carrying capacity, and benefits, so that the scenic spot can develop sustainably under the condition of grasping the carrying capacity and restrictive conditions. This paper combines the set pair analysis method to evaluate the ecological tourism carrying capacity of scenic spots, so as to improve the quantitative effect of ecological tourism carrying capacity of scenic spots. In addition, this paper introduces the fuzzy analytic hierarchy process to determine the weight of the evaluation indicators and combines the set pair analysis method to establish a comprehensive evaluation model. The research results show that the evaluation method of ecotourism carrying capacity of popular scenic spots based on set pair analysis proposed in this paper has a good effect.